Introduction Of Early Prominent Sīrah Writings - Javid Ahmad Bhat (Fakultas Agama Islam Universitas Wiralodra, 2023)
The tradition of Sīrah writing goes back to the very generation of companions of Prophet Muhammad (SAAS). The very first Sīrah works that appeared distinct from the hadith works, however, did not deal with complete biography of Prophet Muhammad (SAAS), rather they addresses aspects of his socio-political life and organisation of the government during the Medinan period. This aspect of Sīrah writing came to be known in history as Maghazi. Though a bit later when comprehensive biographies of the Prophet Muhammad (SAAS) were compiled al-Maghazi were also incorporated in the Sīrah works, socio-political aspect of the Prophet’s life especially his conduct was entities of his time remained focus of various Sīrah works. A large number Sīrah works have been written by scholars from different perspectives highlighting different dimensions of it both in the past and in the contemporary times. In this paper the scholar revived few important books, written during early period of Islam.